PLANNING WATER SUSTAINABLE URBAN AND INFRASTRUCTURE DEVELOPMENT IN WATER-SCARCE REGIONS: AN ANALYSIS OF PLANNING POLICIES IN THE CITY OF WINDHOEK - Shefika, Nestor (2023)
Geography and Environmental Studies